Ag-Pd alloy decorated ZnIn2S4 microspheres with optimal Schottky barrier height for boosting visible-light-driven hydrogen evolution. (1st July 2022) - Liu, Chao; Zhang, Yulong; Wu, Jiaxin; Dai, Hailu; Ma, Chengjian; Zhang, Qinfang; Zou, Zhigang
Highlights: Ag-Pd alloy/ZnIn2 S4 microspheres were achieved by a chemical reduction method. Ag-Pd alloy loading enhanced light-absorption and charge separation of ZnIn2 S4 . Ag-Pd/ZIS composites showed the excellent photocatalytic H2 evolution performance. Appropriate Schottky barrier height benefited the charge carrier separation. Theoretical calculation and experimental verification confirmed optimal Ag-Pd alloy. Abstract: Rapid charge carrier recombination rate and insufficient light harvesting capacity are two dominating drawbacks encountered in zinc indium sulfide (ZnIn2 S4 ) for photocatalytic applications. Herein, a chemical reduction method was performed to combine bimetallic Ag-Pd alloy nanoparticles (NPs) with spherical-like ZnIn2 S4 (ZIS). By optimizing Ag:Pd molar ratio and overall loading amount, the optimal Ag0.25 Pd0.75 -ZIS sample exhibited a maximum H2 evolution rate (125.4 µmol/h) under visible light, which was higher than that of ZIS, Ag-ZIS and Pd-ZIS. The loading of Ag NPs contribution to PHE reaction by its plasmonic effect was negligible compared to that of Pd loading (Schottky effect). The apparent quantum yield (AQY) values over Ag0.25 Pd0.75 -ZIS sample could reach up to 18.3% at 400 nm and 15.8% at 420 nm. The enhanced activity for photocatalytic hydrogen evolution (PHE) over Ag0.25 Pd0.75 -ZIS sample was mainly due to the bimetallic synergistic effect that presented as follows. Firstly, the plasmon hybridization by loading Ag-Pd bimetallic alloy can significantly increase light harvesting capacity of ZIS. Secondly, the optimal Schottky barrier height formed between Ag-Pd alloy and ZIS interface was beneficial for prolonging electron-hole pair lifetimes, promoting charge carrier separation and thus facilitating PHE efficiency. Density functional theory (DFT) analysis indicated that the adsorption energy of H* over Pd0.75 Ag0.25 alloy was very close to zero and thus theoretically possessed the highest activity for H2 evolution, which is in line with experimental results. Combined theoretical calculation with experimental results, a reasonable photocatalytic mechanism was proposed and verified.